Analysis of secondary metabolite gene and protein expression profiles in Streptomyces coelicolor grown under environmental conditions. - Kathryn Laura Bell (2012)
Streptomycetes are Gram positive, soil dwelling filamentous bacteria, known for their production of secondary metabolites. Genome sequencing of Streptomyces coelicolor identified 26 known or predicted secondary metabolite gene clusters ranging from antibiotics to siderophores, lipids, pigments and lantibiotics. Most studies investigating secondary metabolite production in Streptomyces, as well as other bacteria, are undertaken in liquid or on solid media. There is little gene expression data available from in situ studies. This study determined expression in a totally different growth medium, soil, to gain insight into growth and adaptation under more 'normal' habitat conditions and the effect changing environmental factors has on the expression of secondary metabolite gene clusters. In order to do this, S. coelicolor was grown in soil microcosms from which RNA was extracted and amplified using an optimised T7 polymerase-based RNA amplification protocol. The amplified RNA was used to determine gene expression profiles via endpoint RT-PCR and RT-qPCR. In a complementary approach, S. coelicolor sand microcosms were subjected to a novel protein extraction procedure to determine protein expression profiles in soil. This study elucidated how carbon, nitrogen and metal availability, the environmentally bioactive entomopathogenic fungus Metarhizium anisopliae and nematode Steinernema kraussei affect secondary metabolite gene expression in soil. In contrast to the consensus of secondary metabolism commencing after reduction or cessation of growth, this study revealed expression of secondary metabolite biosynthetic genes and proteins related to secondary metabolism before the onset of exponential growth. Some secondary metabolite genes/proteins were even expressed constitutively. Soil microcosms have been shown to be an important tool for gene expression analysis. The results of these novel transcriptomic and proteomic approaches therefore have given new insight into secondary metabolism and its role under natural habitat conditions.